2020
DOI: 10.21203/rs.3.rs-50761/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dysregulation of the hypothalamic-pituitary-adrenal axis in diet-induced prediabetic male Sprague Dawley rats

Abstract: Background: Altered function of the hypothalamic-pituitary-adrenal (HPA) axis in type 2 diabetic patients, a condition preceded by pre-diabetes, has been shown to increase the risk of depression as well as cause downstream effects resulting in upregulation of gluconeogenesis and dyslipidemia. In addition, stress, either psychological from managing diabetes or lifestyle related, further activates the HPA axis causing an exaggerated stress response. This study investigated the activity of the HPA axis in selecte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…An excessive fructose intake crosses the blood-brain barrier (BBB) through glucose transporter 5 and accumulates in the hypothalamus. 25 This leads to excessive activation of the HPA axis and increased cortisol secretion, which increases the risk of depression. 25 In a double-blind, randomized and placebo-controlled clinical trial, compared with the placebo group, urinary cortisol levels in the prebiotic and probiotic groups decreased by 19% and 20%, respectively.…”
Section: Dysregulation Of the Hpa Axismentioning
confidence: 99%
See 1 more Smart Citation
“…An excessive fructose intake crosses the blood-brain barrier (BBB) through glucose transporter 5 and accumulates in the hypothalamus. 25 This leads to excessive activation of the HPA axis and increased cortisol secretion, which increases the risk of depression. 25 In a double-blind, randomized and placebo-controlled clinical trial, compared with the placebo group, urinary cortisol levels in the prebiotic and probiotic groups decreased by 19% and 20%, respectively.…”
Section: Dysregulation Of the Hpa Axismentioning
confidence: 99%
“…25 This leads to excessive activation of the HPA axis and increased cortisol secretion, which increases the risk of depression. 25 In a double-blind, randomized and placebo-controlled clinical trial, compared with the placebo group, urinary cortisol levels in the prebiotic and probiotic groups decreased by 19% and 20%, respectively. 26 Furthermore, panaxynol can inhibit the dysregulation of the HPA axis by inhibiting the content of the CRH in the hypothalamus and increasing the expression of the GR.…”
Section: Dysregulation Of the Hpa Axismentioning
confidence: 99%
“… 13 Patients with diabetes have increased HPA axis activation. 14 According to, 15 there might be a link between stress, diabetes, and plasma cortisol levels. Cortisol and testosterone levels in T2DM patients and controls were to be compared as part of this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that T2DM related complications begin during prediabetes [23,24]. Studies in our laboratory using the high-fat-high-carbohydrate (HFHC) diet-induced model of prediabetes have demonstrated that kidney and brain injury occurs during prediabetes [25,26]. However, any injury to the myocardium during prediabetes have not been investigated.…”
Section: Introductionmentioning
confidence: 99%